2016
DOI: 10.1074/jbc.m116.739342
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and Anion Selectivity of Volume-regulated Anion Channels (VRACs) Depend on C-terminal Residues of the First Extracellular Loop

Abstract: Canonical volume-regulated anion channels (VRACs) are crucial for cell volume regulation and have many other important roles, including tumor drug resistance and release of neurotransmitters. Although VRAC-mediated swelling-activated chloride currents (I Cl,vol ) have been studied for decades, exploration of the structure-function relationship of VRAC has become possible only after the recent discovery that VRACs are formed by differently composed heteromers of LRRC8 proteins. Inactivation of I Cl,vol at posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 29 publications
(51 reference statements)
6
81
0
Order By: Relevance
“…13,14,20,30 LRRC8 family consists of 5 members denoted as A, B, C, D and E. LRRC8E was found to be one of the essential VSOR components necessary for its rapid inactivation at high depolarizing positive potentials in human colonic tumor HCT116 cells. 13,31 In our experiments, coexpression of LRRC8A with LRRC8E or overexpression of LRRC8E alone did not affect significantly the amplitude of VSOR currents in KCP-4 cells (Fig. 4D).…”
Section: Lrrc8a/d/e Is Abundantly Expressed In a Vsor-deficient Cell mentioning
confidence: 50%
“…13,14,20,30 LRRC8 family consists of 5 members denoted as A, B, C, D and E. LRRC8E was found to be one of the essential VSOR components necessary for its rapid inactivation at high depolarizing positive potentials in human colonic tumor HCT116 cells. 13,31 In our experiments, coexpression of LRRC8A with LRRC8E or overexpression of LRRC8E alone did not affect significantly the amplitude of VSOR currents in KCP-4 cells (Fig. 4D).…”
Section: Lrrc8a/d/e Is Abundantly Expressed In a Vsor-deficient Cell mentioning
confidence: 50%
“…Together with the presence of five different LRRC8 genes, which are often coexpressed in the same cell, a hexameric assembly suggests that there could be a large number of differently composed VRAC channels that may have different properties. Indeed, the LRRC8 subunit composition determines the voltage-dependent inactivation of VRAC currents at non-physiological, inside-positive potentials (Ullrich et al, 2016;Voss et al, 2014), and their single-channel amplitudes (Syeda et al, 2016). Furthermore, the LRRC8D subunit is crucial for the VRAC-mediated cellular uptake of blasticidin S (Lee et al, 2014) and of the anti-cancer drugs cisplatin and carboplatin (Planells-Cases et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, standard systems like HEK or CHO cells endogenously express VRAC, requiring LRRC8 gene-knockout cell lines for mechanistic investigations 6,15 We have recently found that Xenopus oocytes represent a convenient expression system for LRRC8 proteins. 16 Un-injected oocytes, or oocytes injected with single LRRC8 subunits had no detectable VRAC currents, whereas co-injection of LRRC8A and 8C, 8D or 8E (but not 8B) RNA yielded typical VRAC currents that slowly activated in hypotonic conditions.…”
Section: Introductionmentioning
confidence: 99%